Molecular line emission from planet-forming Herbig Ae disks. Issue Volume 15:Issue S350(2019) (April 2019) - Booth, Alice S.; Walsh, Catherine
Abstract: We present ALMA observations of four different molecular species in showcasing their potential as tracers of physical and chemical conditions in planet forming Herbig Ae disks.